Continuous Monitoring of Lettuce Growth in Hydroponic System - Arvind Kumar G, Sowmya N, Vanitha K. M, Sharan Reddy (Mathematical Statistician and Engineering Applications, 2022)
In good old days, traditional farming was in practise where soil was the medium for cultivation. Soil based agriculture uses pesticides to eliminate soil borne pests and disease, as the crops are harmed by insects and few crops are affected by diseases. The crops must be protected against pests and insects to get maximum yield [1]. Use of pesticides can cause soil erosion, air and water pollution. Disease in plant can also cause loss in production and economy hence to overcome this issue plant has to be monitored continuously. If disease is identified earlier, preventive measure can be taken. In this paper, hydroponic system is setup and lettuce are grown in the nutrient rich solution. Essential parameters like pH, EC, temperature of the nutrient solution is also monitored every day. The machine learning algorithm is built using MATLAB. The features are extracted using GLCM of both healthy and unhealthy. Using CNN convolutional neural network algorithm, the leaf is classified either as healthy or unhealthy.